Effects of convergent–divergent vortex finders on the performance of cyclone separators using computational fluid dynamics simulations. (January 2020) - Kumar, Vikash; Jha, Kailash
This study investigates the effect of convergent–divergent vortex finders on the performance of cyclone separators, which is measured in terms of pressure drop and collection efficiency. Six cyclone models (two with uniform diameter and four with convergent–divergent vortex finders) were numerically simulated. The numerical simulations have been carried out using the commercial computational fluid dynamics code (CFD) Fluent v15. The simulation procedure has been validated using experimental data from the published literature where a good agreement between the numerical results and the experimental data is seen. A grid independence test has been carried out by using two levels of grids for correctness of our simulation. The Reynolds averaged Navier–Stokes (RANS) and continuity equations have been solved for the flow simulation. The Reynolds stress model is used for modeling the stress tensor and closing the RANS equations. The results show that a convergent–divergent vortex finder is capable of producing better performance (pressure drop and collection efficiency) than the uniform diameter cyclones. Only one performance parameter can be improved in uniform diameter cyclones. In comparison to the standard uniform vortex finder cyclones, the convergent–divergent vortex finder improves the pressure drop by 6% and also reduces the cut-size to 1.4 from 1.6 µm. It is further seen that decreasing the throat area or increasing only the lower diameter of the vortex finder causes the performance to degrade. This study proves that convergent–divergent instead of uniform diameter vortex finders can be used in gas cyclones for obtaining a better performance with the same geometry.